Factors determining the home ranges of pet cats: A meta-analysis. (November 2016) - Hall, Catherine M.; Bryant, Kate A.; Haskard, Kathy; Major, Taryn; Bruce, Sarah; Calver, Michael C.
Abstract: Roaming pet cats Felis catus are a significant conservation issue because they may hunt, harass and compete with wildlife; spread disease, interbreed with cats in feral populations, and hybridise with wild native felids. Studies of the roaming behaviour of pet cats are often hampered by modest sample sizes and variability between cats, limiting statistical significance of the findings and their usefulness in recommending measures to discourage roaming. We resolved these difficulties through meta-analyses of 25 studies from 10 countries involving 469 pet cats to assess the influence of sex, whether a cat was desexed and housing density on roaming. A complementary linear mixed models approach used data on 311 individual animals from 22 studies and was also able to assess the influence of age and husbandry practices on roaming. This restricted sample gave greater statistical power than the meta-analyses. Meta-analyses found that: male pet cats had larger home ranges than females, desexing did not influence home range, and cats had larger home ranges when housing densities were low. The linear mixed models supported those results. They also indicated that animals ≥ 8 years old had smaller home ranges than younger cats. Cats fed regularly, provided with veterinary care and socialised with humans had similar home ranges to cats living in association with households but not provided for in some of these ways. Short of confinement, there is no simple measure owners can adopt to reduce roaming by their cats and prevent the associated environmental problems. Highlights: We assessed pet cats' roaming behaviour using meta-analyses and mixed linear models. Desexing, regular feeding and interaction with owners did not affect home range. Males had larger home ranges than females. Both sexes had larger home ranges at low housing densities. Confinement remains the simplest measure to reduce roaming by pet cats.